SPIRITUAL AND MORAL EDUCATIONAL ASPECTS OF SUFISM (World Conference on Agricultural and Earth Sciences, 2026)
This article analyzes the spiritual and educational activities of the prominent representatives of the Mawarannahr Sufi tradition — Mawlana Orif Deggarani and Bahauddin Naqshband. Their ideas on moral education, spiritual purification, and the formation of the Perfect Human Being (al-insān al-kāmil) are examined in detail. The article also highlights their place in Sufi philosophy, their traditions of mentoring disciples, and their contribution to social development. In addition, the contemporary relevance of Sufi teachings is emphasized.
Keywords: Mawlana Orif Deggarani, Bahauddin Naqshband, Sufism, spirituality, enlightenment, perfect human being, spiritual education, Naqshbandiyya order